Employed but not included: the case of consumer-workers in mental health care services. Issue 15 (22nd August 2021) - Edan, Vrinda; Sellick, Kathryn; Ainsworth, Susan; Alvarez-Varquez, Susie; Johnson, Brendan; Smale, Krystyn; Randall, Rory; Roper, Cath
Abstract: This article explores how employees with mental illness perceive HRM and its impact, drawing on consumer-centred perspectives. Using the case of consumer-workers employed for their lived experience of mental illness in mental health care services, we investigate the degree to which they feel included or marginalised by HR systems, processes and practices. Through a mixed method study designed along co-production principles, we found consumer-workers faced different but interrelated problems stemming from their status: a general lack of understanding of the role and its purpose; inequity in pay rates, workplace conditions, and training and development; as well as employment precarity and difficulties around disclosure, stigmatisation and discrimination. Overall, organisational support for these unique roles seemed to be lacking despite the clear business need for these positions. We make several contributions: firstly, we show how employees in a unique role that requires experience of mental illness are impacted by the interaction between HR systems, processes and practices; secondly, we illustrate why HR scholars need to engage with varied paradigms of knowledge about mental illness beyond the dominant medical/psychiatric one; and thirdly, we demonstrate a methodology that not only explores employee perspectives, but includes employees in the research design and process.